HIP 67506 C: MagAO-X confirmation of a new low-mass stellar companion to HIP 67506 A. Issue 3 (21st March 2023) - Pearce, Logan A; Males, Jared R; Haffert, Sebastiaan Y; Close, Laird M; Long, Joseph D; McLeod, Avalon L; Knight, Justin M; Hedglen, Alexander D; Weinberger, Alycia J; Guyon, Olivier; Kautz, Maggie; Van Gorkom, Kyle; et al.
ABSTRACT: We report the confirmation of HIP 67506 C, a new stellar companion to HIP 67506 A. We previously reported a candidate signal at 2λ/D (240 mas) in L ′ in MagAO/Clio imaging using the binary differential imaging technique. Several additional indirect signals showed that the candidate signal merited follow-up: significant astrometric acceleration in Gaia DR3, Hipparcos–Gaia proper motion anomaly, and overluminosity compared to single main-sequence stars. We confirmed the companion, HIP 67506 C, at 0.1 arcsec with MagAO-X in 2022 April. We characterized HIP 67506 C MagAO-X photometry and astrometry, and estimated spectral-type K7-M2; we also re-evaluated HIP 67506 A in light of the close companion. Additionally, we show that a previously identified 9 arcsec companion, HIP 67506 B, is a much further distant unassociated background star. We also discuss the utility of indirect signposts in identifying small inner working angle candidate companions.